When winning costs your peace: How does vertical individualism Hijack relaxation capacity? Network analysis and mediation models - Wenyan Cheng; Ling Cheng; Zhichao Qian; Haoyu Wang (PLoS ONE, 2025)
In the context of increasing competition, the phenomenon of individuals experiencing guilt or anxiety at rest has become more pronounced, particularly among Chinese university students. While previous research has primarily explained this phenomenon from the perspective of collectivist cultures, this study posits that vertical individualism may offer a more compelling explanation. A sample of 550 Chinese university students was surveyed to collect data on vertical/horizontal individualism-collectivism, status anxiety, and rest intolerance. A partial correlation network analysis, controlling for demographic covariates, was conducted to explore the psychological structure of these constructs. The results identified Vertical Individualism (VI) and Status Anxiety (SA) as the core bridge nodes connecting the community of cultural values to the dimensions of rest intolerance. Subsequent mediation analyses confirmed that SA partially mediated the relationship between VI and overall rest intolerance. This indirect effect was particularly pronounced for the affective and social-comparative components of the phenomenon. These findings challenge traditional collectivist frameworks and reveal a nuanced psychological mechanism: competitive cultural values exacerbate rest intolerance through the pathway of status anxiety. This provides novel theoretical insights for psychological interventions and cultural adaptation education in higher education settings.